A review on family-controlled business groups with particular reference to corporate governance in Malaysia - Ng, Sin Huei; Teh, Boon Heng; Ong, Tze San; Soh, Wei Ni (Medwell Journals, 2014)
Within the publicly-listed corporate sector, forming business groups is a common practice in family businesses in Malaysia. The formation of business groups by controlling families can bring additional agency problems which do not exist in Anglo-Saxon countries, particularly in the US and UK corporations. The expanded control over a number of listed member firms made possible by business groups increases the chances of expropriation of minority shareholders. The more complicated the structure of the business group, the more serious the problem may be. This is especially true in Malaysia where it is widely known that the controlling families of many business groups, particularly the large ones have close relationship with influential senior politicians or government officials. The relationship provides political patronage and protection to facilitate the expropriation activities by the owner-managers. The principal-principal problems can therefore, be more serious. Thus, more understanding of the agency problems facing family-controlled firms can be achieved by examining the business group affiliation issue in some detail.